The link between turbulence, magnetic fields, filaments, and star formation in the central molecular zone cloud G0.253+0.016 - Federrath, Christoph; Kruijssen, Diederik (Arxiv, 2016)
Star formation is primarily controlled by the interplay between gravity, turbulence, and magnetic fields. However, the turbulence and magnetic fields in molecular clouds near the Galactic Center may differ substantially from spiral-arm clouds. Here we determine the physical parameters of the central molecular zone (CMZ) cloud G0.253+0.016, its turbulence, magnetic field and filamentary structure. Using column-density maps based on dust-continuum emission observations with ALMA+Herschel, we identify filaments and show that at least one dense core is located along them. We measure the filament width W_fil=0.17$±$0.08pc and the sonic scale λ_sonic=0.15$±$0.11pc of the turbulence, and find W_fil~λ_sonic. A strong velocity gradient is seen in the HNCO intensity-weighted velocity maps obtained with ALMA+Mopra, which is likely caused by large-scale shearing of G0.253+0.016, producing a wide double-peaked velocity PDF. After subtracting the gradient to isolate the turbulent motions, we find a nearly Gaussian velocity PDF typical for turbulence. We measure the total and turbulent velocity dispersion, 8.8$±$0.2km/s and 3.9$±$0.1km/s, respectively. Using magnetohydrodynamical simulations, we find that G0.253+0.016's turbulent magnetic field B_turb=130$±$50$\m is only ~1/10 of the ordered field component. Combining these measurements, we reconstruct the dominant turbulence driving mode in G0.253+0.016 and find a driving parameter b=0.22$±$0.12, indicating solenoidal (divergence-free) driving. We compare this to spiral-arm clouds, which typically have a significant compressive (curl-free) driving component (b>0.4). Motivated by previous reports of strong shearing motions in the CMZ, we speculate that shear causes the solenoidal driving in G0.253+0.016 and show that this reduces the star formation rate (SFR) by a factor of 6.9 compared to typical nearby clouds.
Gesehen am 27.10.2017